Student-Centered Approach in Primary Mathematics: Teachers' Perceptions and Practices in Rural Cambodia - Pei Miao; Por Vutha (Srawung: Journal of Social Sciences and Humanities, 2026)
The successful implementation of student-centered pedagogy in primary mathematics education is fundamentally contingent upon teachers' perceptions and instructional practices, particularly within developing country contexts undergoing curriculum reform. This study examined the perceptions and classroom practices of primary mathematics teachers regarding the adoption of the Student-Centered Approach (SCA) in rural and remote public primary schools in Siem Reap Province, Cambodia. Employing a qualitative case study design guided by phenomenological principles, data were collected through semi-structured individual interviews and non-participant classroom observations with four purposively selected female primary mathematics teachers representing both experienced and newly qualified practitioners across rural and remote school settings. Thematic content analysis was applied to identify patterns across interview transcripts and observational field notes. The findings indicate that all participants demonstrated a broadly consistent conceptual understanding of SCA principles; however, a notable gap was observed between their stated perceptions and enacted classroom practices. Experienced teachers implemented SCA more effectively and consistently than their newly qualified counterparts, a disparity attributed primarily to differences in professional development access, teaching experience, and individual motivation rather than geographic location or formal educational background. Systemic barriers including classroom overcrowding, insufficient instructional materials, and inequitable distribution of in-service training opportunities were identified as significant constraints on effective SCA adoption. The study concludes that sustainable pedagogical reform in resource-limited primary school contexts requires coordinated investment in teacher professional development equity alongside structural improvements in school-level resources and institutional support.